Ethics for our times essays in Gandhian perspective - Nadkarni, M. V. (New Delhi : Oxford University Press, 2011)
'Ethics for our Times' presents a comprehensive analysis of ethics as a conceptual framework and as a guide to action in tackling the problems of modernizing societies. It examines the relevance of Gandhian approach to current issues like environmental crisis, social justice, and equity and harmony in society.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Ethics; Gandhi, -- Mahatma, -- 1869-1948.